Daya Ledak Otot Tungkai Terhadap Kemampuan Momtong Dollyo Chagi Taekwondoin Se-Kabupaten Kepahiang - Dika Erwina; Zarwan Zarwan; Suwirman Suwirman; Arie Asnaldi; Yaslindo Yaslindo (Ilmu Olahraga, 2022)
The problem in this study is the lack of momtong dollyo chagi ability of Taekwondo athletes, this is caused by many factors, but researchers only look at the explosive power of the leg muscles. This study aims to determine the relationship between limb muscle explosive power and the ability of momtong dollyo chagi in Tekwondoin in Kepahiang Regency. This research is a type of correlational research. The population in this study were Taekwondo athletes in Kepahiang Regency. The sampling technique in this study is the purposive sampling technique, so that a sample of 25 people is obtained from male athletes and female athletes. The data was collected using a standing board jump test for leg muscle explosive power and a momtong dollyo chagi test within 30 seconds for the ability of momtong dollyo chagi as a target. The data was processed using the product moment correlation technique. There is a significant difference between leg muscle explosive power and the ability of male athletes with a contribution of 0.752 with a determination of 56% and female athletes with a contribution of 0.645 with a determination result of 40%.